RETRACTED: Obesity Accelerates Leukocyte Telomere Length Shortening in Apparently Healthy Adults: A Meta-Analysis - Khosravaniardakani, Sheida; Bokov, Dmitry Olegovich; Mahmudiono, Trias; Hashemi, Seyedeh Sedigheh; Nikrad, Negin; Rabieemotmaen, Shadi; Abbasalizad-Farhangi, Mahdieh (Frontiers in Nutrition, 2022)
Background: Shorter telomere length is associated with numerous comorbidities. Several studies have investigated the role of obesity in telomere shortening. In the current systematic review and meta-analysis, we summarized the results of studies that evaluated the association between obesity and telomere length. Methods: A systematic search from Scopus, PubMed, Embase, and Proquest electronic databases up to 19 August 2021 without language restriction was performed and after data extraction and screening, 19 manuscripts were eligible enough to be included in the final meta-synthesis. Results: Being at the highest category of telomere length was associated with approximate 0.75 kg/m2 reduction in BMI (WMD= -0.75 kg/m2; CI= -1.19, -0.31; P < 0.001; I2 = 99.4%). Moreover, individuals with overweight/obesity had 0.036 kBP shorter telomere length compared with adults without overweight/obesity (WMD: -0.036; CI=-0.05, -0.02; P = 0.030; I2= 100%). According to the results of subgroupings, continent, age, and sample size could be possible sources of heterogeneity. Conclusion: According to the results, obesity was associated with shorter telomere length. Because of the observational design of included studies, the causality inference of results should be done with caution, thus, further longitudinal studies are warranted for better inference of causal association.